Assessment of Rainfall Variability and the Impact of Drought on Crop Growth in the Plain and Hill Zones of Uttarakhand, India - Shubhika Goel; R K Singh (Archives of Current Research International, 2025)
The rainfall data for the two stations i.e., Pantnagar (1981-2020) and Ranichauri (1985-2020) have been utilized to study the climate suitable for the growth and development of the crops in the plain and hill zones of Uttarakhand. The pentadal weekly, monthly and seasonal rainfall & rainy days have been calculated for these regions. An increasing trend in the pentadal mean rainfall and rainy days was experienced in the winter and southwest monsoon season and a decreasing trend could be observed in the summer and northeast monsoon season for both the stations. The frequency of meteorological drought for the plain zone is more as compared to hill zone. The Agricultural drought (Kharif & Rabi season) & Heavy rainfall events (at particular date of year) were assessed and there is no drought in the Rabi season for both these regions. The study underscores the importance of continuous climate monitoring, improved irrigation planning, and flood control measures to mitigate the impacts of rainfall variability in Uttarakhand. Adaptive climate strategies must be implemented to ensure sustainable water resource management and agricultural productivity in the region.